Differences Hematology Profiles between Preeclampsia Patient with Normotensive Pregnancy in Dumai Hospital - Miranda Syilvia; Donaliazarti; May Valzon (CV. AKBAR PUTRA MANDIRI, 2025)
Introduction: Preeclampsia is hypertension after 20 weeks gestation, characterized by systolic >140 mmHg or diastolic >90 mmHg in 2 examinations with an interval at least 4 hours in women whose blood pressure was previously normal, accompanied by proteinuria. Preeclampsia is the highest cause of maternal mortality in Indonesia. Changes in the hematological profile in preeclampsia occur due to hemoconcentration, inflammatory processes, thrombocyte activation, and thrombocyte coagulation. Objective: This research aims to determine the difference in hematological profile between preeclampsia patients and normotensive pregnancy at dr. Suhatman MARS Dumai Hospital. Method: This study was analytic observational research with a cross sectional approach, which conducted at dr. Suhatman MARS Dumai Hospital in January – June 2024. The sample of this study is all preeclampsia patients (mild and severe preeclampsia) and normotensive pregnancy recorded in medical records for the 2022-2023 period, who meet the inclusion and exclusion criteria. Hematology profile data (hemoglobin, hematocrit, erythrocyte, leukocyte, and thrombocyte) were tested for normality and homogeneity. The difference in hematology profile between mild preeclampsia, severe preeclampsia, and normotensive pregnancy were analyzed by the ANOVA one-way test. Results: Mild preeclampsia group had the lowest mean hemoglobin level, which was 11.43 gr/dl. Severe preeclampsia group had the lowest mean hematocrit levels and erythrocyte count with values of 32.30% and 3.91 million/mm3, respectively. The highest mean leukocyte count and the lowest mean thrombocyte count were found in normotensive group among which 12,778/mm3 and 232,565/mm3, respectively. Statistical test showed there was no significant difference between mild preeclampsia, severe preeclampsia, and normotensive group in hemoglobin levels (p=0.864), hematocrit levels (p=0.326), erythrocytes count (p=0.191), leukocytes count (p=0.422), and thrombocyte count (p=0.287). Conclusion: There was no significant difference in hematology profile (hemoglobin, hematocrit, erythrocytes, leukocytes, and thrombocyte) between preeclampsia patient and normotensive pregnancy at dr. Suhatman MARS Dumai Hospital.